A RESSIGNIFICAÇÃO DA PROFISSÃO CONTÁBIL: UMA ANÁLISE A PARTIR DA PERSPECTIVA DA CONSTRUÇÃO DE SENTIDO - Peiter, Sandra Laci (2023)
Technological innovations, the globalisation of the economy and changes in legislation through the process of convergence with international standards have affected the work processes and profile of the accountant. New skills have been required, resulting in accountants having to adapt both in their work processes and in their own performance as accountants. It is therefore necessary for this professional group to understand their profession, interpret it and give new meaning to this reality due to the changes that are transforming the profession itself. In this context, in this study we wanted to understand how accountants create meaning and redefine their profession based on the perceived changes in accounting practise. To understand this process, the lens of sensemaking can shed light on how this redefinition of the accounting profession takes place. Sensemaking means "creating meaning", which occurs primarily when unexpected events need to be explained. Through social interaction, seeking mutual understanding, in plausible ways and to minimise ambiguity or uncertainty, the construction of meaning takes place. While sensegiving is the process of persuasion and acceptance of the new vision by others, it is the means of influencing the construction of meanings through the redefinition of reality. We adopted a qualitative, interpretive approach with analysis from a rhizomatic narrative perspective to understand the fragmented nature of reality and the different perceptions of accountants in constructing the meaning of the profession itself. Data collection was done through semi-structured interviews with 28 (twenty-eight) accounting professionals working in different regions of Brazil. The interviews made it possible to hear the different narratives in the form of ante-narrative fragments and to understand the meaning or significance that the changes in the accounting profession represent for each interviewee through their understanding of the reality of the accounting profession. From the perspective of the accountant and his perception and meaning of the accountancy profession, we have tried to identify the contextual changes in the accounting universe, their influences on the work routine and on the socially accepted profile of these professionals, as well as their expectations for the future of the profession. According to accountants, the changes have increased the responsibilities of accountants and have also led to uncertainty and insecurity in relation to the responsibilities imposed on them, constant changes in legislation, advances in technology and the constant need for updating in order to remain active in the market for accounting services. By looking back and looking forward, accountants try to explain what has changed to show how, in complex and ambiguous moments, they have thought about their profession in the face of change and how this is reflected in their working reality, in their profile and in the way they will work in the future. Thus, the accounting profession, like other social processes, goes through the construction of meaning and significance for its constitution, even if this is done in a fragile and unstable way. This illustrates the process of alienation and construction of meaning to which the accountant is subjected, i.e. the way the accountant perceives and makes sense of what is happening, and the way he acts from the moment he has accepted and internalised the changes and begins to understand this as part of his work as an accountant, not individually but collectively, in order to justify that work. And the meanings that emerge from this interaction of the 'accountant self' with the exogenous elements that create pressures, such as the technological and legal changes that have emerged and that have been incorporated into this model of the 'accountant self', relate to the roles that these changes require. So, there is a mobilisation for meaning-making and interpretation of the profession, i.e. for making sense of what it means to be an accountant, i.e. the specialist accountant or the generalist accountant who knows a little bit about everything, or even the network manager, the consultant or the government actor, roles that the accountant believes he has to take in order to define who he is and how he should act.